ASOSIASI ECHINODERMATA DENGAN KOMUNITAS PADANG LAMUN DI PERAIRAN DESA MANGON KECAMATAN SANANA KABUPATEN KEPULAUAN SULA - Syakirin Bilmona; Erly Y. Kaligis; Billy Th. Wagey; Fitje Losung; Natalie D.C. Rumampuk; Lawrence J.L. Lumingas (Sam Ratulangi University, 2023)
The purpose of this study was to determine the association between the phylum Echinodermataand the seagrass community in the waters of Mangon Village. This research was conducted in thewaters of Mangon Village, Sanana District, Sula Islands Regency in October 2022. The researchmethod used was the quadratic transect method. This method consists of 2 research stations which areabout 500m apart. The transect line is drawn straight from the beach to the sea for 100m then aquadratic plot is placed in a zig-zag manner to the left and right of the transect line. There were 10 plotsthat were observed and spaced 10m each and 3 repetitions were carried out with a distance of 50m pertransect. From this method the results obtained in the waters of Mangon Village showed that at stationone, the species found at two stations in Mangon Village waters were 7 species of Echinodermata and6 species of seagrass. Based on the person product moment correlation value, there is a correlation inthe form of a positive association between seagrasses and echinoderms at the study site. Theenvironmental parameters owned by the waters of Mangon Village, Sula Islands Regency, namely,temperature has a range of 24-28˚C, salinity has a range of 28 – 340/00, and pH has a range of 7,08-8,08. The substrate obtained is sand and sand mixed with coral fragments.Keywords: Association of Echinodermata with Seagrass Community, Mangon Village Waters ABSTRAKTujuan penelitian ini adalah untuk mengetahui asosiasi antara filum Echinodermata denganKomunitas padang lamun di perairan Desa Mangon. Penelitian ini dilakukan di perairan Desa MangonKecamatan Sanana Kabupaten Kepulauan Sula pada bulan Oktober 2022. Metode penelitian yangdigunakan adalah metode transek kuadrat, Dalam metode ini terdiri dari 2 stasiun penelitian yangmemiliki jarak sekitar 500m. Garis transek ditarik lurus dari pantai menuju laut sepanjang 100mkemudian diletakkan plot kuadrat secara zig-zag disamping kiri-kanan pada garis transek. Terdapat 10buah plot yang diamati dan diberi jarak masing-masing 10m dan dilakukan sebanyak 3 kalipengulangan dengan jarak 50m per transek. Dari Metode tersbut hasil yang didapatkan di perairanDesa Mangon menunjukan bahwa pada stasiun satu, Spesies yang ditemukan pada dua stasiun diPerairan Desa Mangon adalah 7 spesies Echinodermata dan 6 spesies lamun. Berdasarkan nilaikorelasi person product moment, terdapat korelasi dalam bentuk asosisasi positif antara lamun danEchinodermata di lokasi penelitian. Parameter lingkungan yang dimiliki oleh perairan Desa MangonKabupaten Kepulauan Sula yaitu, suhu memiliki kisaran 24-28˚C, salinitas memiliki kisaran 28 - 340/00,dan pH memiliki kisaran 7,08-8,08. Substrat yang di dapat yaitu pasir dan pasir bercampur pecahankarang. Kata Kunci: Asosiasi Echinodermata, Komunitas Padang Lamun, Perariran Desa Mangon